Language, Ecology and the Future:A Futurological Perspective on Ecolinguistic - Ayuanita, Kristanti; Nugroho, Himmawan Adi; Mustofa, Ali (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study explores how ecolinguistics and futurology can be integrated into English language learning through a contextual and culturally responsive approach. The focus of this study is the Foreign Language Development Programme (FLDP) at UIN Madura, specifically the English language module that discusses traditional herbal medicine as an important part of the traditional knowledge of the Madurese community. Using a qualitative descriptive method, data was collected through content analysis and interviews with lecturers and students. The results of the study indicate that the integration of ecolinguistic content can improve vocabulary mastery, foster environmental awareness, and strengthen students’ cultural identity. Learning materials that highlight local ecological knowledge encourage critical thinking skills, cultural pride, and active student participation. Despite challenges in implementation, such as the need for more local materials and training for lecturers or tutors, ecolinguistic-based English language learning has proven to be an effective pedagogical strategy in creating sustainable education rooted in local culture. Through an ecological approach, it demonstrates that students are not only language learners but also environmentally conscious global citizens proud of their culture.